2012
DOI: 10.1162/jocn_a_00242
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenology of Error Processing: The Dorsal ACC Response to Stop-signal Errors Tracks Reports of Negative Affect

Abstract: Abstract■ A reliable observation in neuroimaging studies of cognitive control is the response of dorsal ACC (dACC) to events that demand increased cognitive control (e.g., response conflicts and performance errors). This observation is apparently at odds with a comparably reliable association of the dACC with the subjective experience of negative affective states such as pain, fear, and anxiety. Whereas "affective" associates of the dACC are based on studies that explicitly manipulate and/or measure the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 58 publications
(71 reference statements)
9
78
1
Order By: Relevance
“…For example, response errors during a flanker task yield larger skin conductance responses and greater heart rate deceleration than correct decisions (Hajcak et al, 2003b), as well as a larger potentiation of the startle reflex (Foti and Hajcak, 2009). These findings suggest that response errors may be perceived as aversive and distressing events (Spunt et al, 2012), which are associated with enhanced arousal and increased activation of the autonomic nervous system (Hajcak et al, 2003b).…”
Section: Interactions Between Affective Processes and Error Monitoringmentioning
confidence: 93%
“…For example, response errors during a flanker task yield larger skin conductance responses and greater heart rate deceleration than correct decisions (Hajcak et al, 2003b), as well as a larger potentiation of the startle reflex (Foti and Hajcak, 2009). These findings suggest that response errors may be perceived as aversive and distressing events (Spunt et al, 2012), which are associated with enhanced arousal and increased activation of the autonomic nervous system (Hajcak et al, 2003b).…”
Section: Interactions Between Affective Processes and Error Monitoringmentioning
confidence: 93%
“…Results from cognitive neuroscience research showing that the dACC is critical for conflict monitoring and discrepancy detection (Botvinick et al 2001) combined with findings from pain and affective neuroscience research showing that the dACC is critical for the unpleasantness of physical pain (Apkarian et al 2005, Eisenberger & Lieberman 2004, Shackman et al 2011 suggest that the dACC may function as a type of neural alarm system (Eisenberger & Lieberman 2004, Spunt et al 2012. For an alarm system (e.g., a smoke alarm) to function properly, two components are needed: a discrepancy detection system that monitors for deviations from desired standards (e.g., too much smoke) and a sounding mechanism (e.g., an alarm bell ringing) that alerts one to the fact that there is a problem that needs to be addressed.…”
Section: The Dacc As a Neural Alarmmentioning
confidence: 99%
“…In addition, functional magnetic resonance imaging (fMRI) studies have shown that dACC responses to cognitive performance tasks are positively correlated with autonomic responses (Critchley et al 2005) and the self-reported desire to avoid a task (McGuire & Botvinick 2010). Finally, a recent study demonstrated that within-subject variability in dACC responses to error trials on a stop-signal task correlated directly with self-reports of negative affective responses to the task (Spunt et al 2012). Thus, across multiple studies, individual differences in neural sensitivity to discrepancies or errors have been shown to correlate directly with various measures of negative affective experience, supporting the alarm system model.…”
Section: The Dacc As a Neural Alarmmentioning
confidence: 99%
“…We additionally included three extra items in both versions of the PANAS: Frustrated, anxious, and unpleasant (along with 'attentive' which is already in the PANAS). The second PANAS administration and added words were used to address concerns raised by Spunt et al (2012) that people are better able to articulate their feelings relative to an actual event and that these particular words were more informative than a broad survey of negative affect.…”
Section: Methodsmentioning
confidence: 99%